Insufficiency of the Cranial Cruciate Ligament, Medial Patellar Luxation and Proximal Valgus Deviation of the Tibia in a Dog - Treatment with Association of Modified TPLO and Double-cut Osteotomy - de Souza Pereira, Lucas; Augusto Lopes Muzzi, Leonardo; Munhoz Garcia Perez Neto, Daniel; Yoiti Kitamura Kawamoto, Fernando; Costa Mancilha Dias, Luana; Pimenta Neves, Mariana; Martins Araujo , Iara; Vinício Chaves, Glauco (Acta Scientiae Veterinariae, 2025)
Background: Cranial cruciate ligament insufficiency (CCLI) is one of the most common causes of lameness in dogs. This debilitating condition typically affects adult large-breed dogs. There is a subset of dogs where CCLI occurs alongside proximal tibial deformity (tibial varus or valgus), tibial torsion, excessive tibial plateau angle, or patellar luxation. A high frequency of reports notes patients with concomitant medial patellar luxation (MPL) and CCLI. The objective of this study is to report the use of combined modified TPLO and double cut medial crescentic closing wedge osteotomy techniques for the treatment of CCLI associated with MPL and proximal tibial valgus deformity in a bitch. Case: A 4-year-old spayed bitch mixed-breed, weighing 9.5 kg, was presented at the Veterinary Hospital of the University (HV-UFLA), Lavras, Brazil, with a 30-day history of left pelvic limb (LPL) lameness. On physical examination, the patient exhibited functional disability with non-weight-bearing lameness of the LPL. Orthopedic examination of the stifle joint revealed CCLI by positive drawer and tibial compression tests. A meniscal click was also observed in the tibial compression test. Additionally, the patella could be medially luxated and was classified as grade 2. Radiographic examinations of the LPL were performed in different projections to identify radiographic findings suggestive of CCLI and to evaluate the angular deviations of the tibia and femur. Radiographic evaluation of the stifle joint revealed cranial displacement of the tibia relative to the femur, suggesting CCLI. The tibial plateau angle (TPA) was calculated and approximated to 29°. Radiographic examination of the tibia in the craniocaudal projection revealed proximal tibial valgus deformity, with an increased mechanical medial proximal tibial angle (mMPTA) of 101°. As a surgical technique for stabilizing the stifle joint with CCLI and correcting MPL and proximal tibial valgus deformity, the modified TPLO technique combined with a double cut medial crescentic closing wedge osteotomy was chosen. The surgical procedure began with medial arthrotomy in the stifle joint to assess the integrity of the menisci, revealing a bucket-handle tear in the caudal pole of the medial meniscus, which led to partial meniscectomy. Corrective ostectomies were then performed. To treat the proximal tibial valgus deformity, a crescent-shaped wedge ostectomy was performed with medial closing using a semicircular oscillating saw, aiming for a mMPTA of 93°. A caudal rotation and medial translation of the proximal tibial segment were then performed to realign the quadriceps extensor mechanism, stabilizing the patella in the femoral trochlear groove. The proximal tibial segment was rotated to achieve a target postoperative TPA of approximately 5°. The ostectomy was then stabilized with a TPLO locking plate. Immediate postoperative radiographs were taken to evaluate implant positioning and measure the angles achieved. A TPA of 5° and a mMPTA of 91° were achieved. At the 1-week postoperative follow-up, significant improvement in lameness was already observed, with partial weight-bearing of the operated limb. Discussion: The results of this case demonstrate that the combination of modified TPLO and a double cut medial crescentic closing wedge osteotomy techniques performed in a single surgical procedure was effective in treating CCLI, proximal tibial valgus deformity, and MPL in a bitch. This approach appears to be a viable option for patients with these comorbidities in the stifle joint. Keywords: dog, tibial osteotomies, tibial plateau, angular bone deformity, small animals, orthopedics. Título: Insuficiência do ligamento cruzado cranial, luxação medial de patela e desvio valgo proximal da tíbia em uma cadela - tratamento com associação de TPLO modificada e de osteotomia duplo corte Descritores: cão, osteotomias tibiais, platô tibial, deformidade angular óssea, pequenos animais, ortopedia.